2017
DOI: 10.1080/24749508.2017.1389454
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and analysis of traffic noise in different zones of Faisalabad – an industrial city of Pakistan

Abstract: Noise is surely one of the most undesirable by-products of the modern mechanized lifestyle. We see the rush and the fights between the masses relating to the traffic laws everywhere, their violations and their after-shocks. To assess the noise levels in busy roads of Faisalabad, a study was conducted at three different times of a day i.e. morning (9:00 am), noon (3:00 pm) and evening (6:00 pm). Out of a total of 85 sites, 6 sites at morning time, 52 sites at noon time and 27 sites at evening time were exceedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…2). This outcome remained consistent in all the categorized areas included in the study and in line with the previous ndings (Doygun et al 2016;Purwaningsih et al 2018). The high tra c density is responsible for high noise pollution (Khan et al 2018), whereas urban noise is signi cantly decreased in low tra c areas (Tezel et al 2019).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…2). This outcome remained consistent in all the categorized areas included in the study and in line with the previous ndings (Doygun et al 2016;Purwaningsih et al 2018). The high tra c density is responsible for high noise pollution (Khan et al 2018), whereas urban noise is signi cantly decreased in low tra c areas (Tezel et al 2019).…”
Section: Discussionsupporting
confidence: 89%
“…It is thought that the excessive noise levels in the urban environment is due to the industries (Bamane et al 2019;Zeydabadi et al 2019), community noise (Picaut et al 2019;Bridger et al 2019;Wilson 2019), and tra c on the roads (Cramer et al 2019;Jørgensen et al 2019;Paiva et al 2019;Cai et al 2019). It was observed from the previous studies that many sites in Faisalabad, Pakistan have SPLeq > 100 dB, which were exceeding the permissible limits of Pakistan Environmental Protection Agency (Farooqi et al 2017). Urban noise is not only the issue in Pakistan, but also in most parts of the world.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Many studies have shown that short-and long-term exposure to noise not only reduces human hearing, but also increases blood pressure, cardiovascular disease, anxiety and insomnia. Thus, noise exposure leads an increase in drug use and visits to hospitals (Farooqi et al 2017). The noise caused by urban traffic can lead to increased heart diseases (Singh et al 2018).…”
Section: Introductionmentioning
confidence: 99%